Pengembangan Sistem Klasifikasi Diagnosa Medis Menggunakan Progressive Web Application Terintegrasi Machine Learning - Muhammad Andika Fadilla; M Fakhri Sholahuddin; Tata Sutabri (Syntax Corporation Indonesia, 2024)
This research aims to present a solution that not only improves efficiency in coding medical diagnoses, but also ensures high accuracy at various levels of case complexity. The classification of medical diagnoses is a crucial aspect of health information management, particularly in coding diagnoses into the ICD-10 and ICD-9CM standards. A Progressive Web Application (PWA) has been developed to automate this process, leveraging Machine Learning technology with the Sentence Transformer model architecture